Influence of socio-economic status in economic empowerment among Iranian farmers - Koohi, Nasrabadi Mohsen; Redzuan, Ma'rof (Rural Organisation for Appropriate Development-ROAD TRUST (R), 2013)
Economic empowerment of farmers is a socioe-conomic process through which farmers are motivated to enhance their belief in self-efficacy, to improve their abilities to control their own resources, to increase their income and to unleash their creative and productive energies to achieve sustainable improvement in their living standards. The farmers must move from being passive recipients of information, services and regulations to a situation where they take full responsibility for their own development and use public and private institutions as resource providers. However, there are many factors which stop farmers benefiting from such development and contribute to farmer's powerlessness such as inequality in economic opportunity, lack of education, knowledge, and skills, lack of access to financial services and lack of access to markets. This study illuminates the relationship between socioe-conomic demographic variables of farmers and their economic empowerment in rural area of Isfahan province, Iran. Indeed, this study discovered the effect of respondents’ background i.e., age, education, annual income, cultivated land size, agriculture experience, year's membership cooperative, and ownership on their economic empowerment. Data was collected from 400 farmers who are the members of 10 agricultural production cooperatives (APC) in Isfahan province. The results of the study showed that among the seven socioe-conomic variables, three had effects on economic empowerment. Among these three, the education had the most effect and played an important role in increasing farmer's economic empowerment. The results, also, showed the impact of annual income and cultivated land size in enhancing economic empowerment of farmers.